Kinematic differences of taekwondo roundhouse kick between Thailand national and youth national athletes - Detjareny, T.; Limroongreungrat, W.; Sinphurmsukskul, O.; Pinthong, M (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to compare kinematic in taekwondo roundhouse kick of Thailand National athletes to Youth National athletes. Both groups experienced and were successful in major international competitions. The athletes were instructed to promptly perform roundhouse kick at the target with their dominant leg when the LEDs above the target were turned on. Motion analysis system captured three kicks. The Mann-Whitney U test did not reveal significant differences of response time and selected kinematic parameters of the kicking leg between the two groups. In conclusion, both groups shows similar kicking pattern; nevertheless, this study only investigated the kick in static condition. Future research should include dynamic condition.